2000
DOI: 10.1038/sj.ejcn.1600886
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectroscopy—a potentially useful method for rapid determination of fat and protein content in homogenized diets

Abstract: Objective: To investigate the potential of near-infrared re¯ectance (NIR) spectroscopy as a rapid and nondestructive method to determine total fat and protein in mixed, homogenized and freeze-dried human diets. Design: 29 students collected duplicate portions of their diet for four consecutive days. In addition, a detailed food diary was kept. The duplicate portions were analysed for total protein and fat content both by traditional chemical analysis (Kjeldahl and Folch methods) and through the recently develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…The 2000–2500 nm region (4000–5000 cm −1 ) has been reported to be useful for the study of protein structure,18,24,28 either to quantify the amount of protein in a particular sample or for protein structural characterization 13–18,28,30. Table 2 summarizes the assignments for the major NIR bands in the 2000–2500 nm region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2000–2500 nm region (4000–5000 cm −1 ) has been reported to be useful for the study of protein structure,18,24,28 either to quantify the amount of protein in a particular sample or for protein structural characterization 13–18,28,30. Table 2 summarizes the assignments for the major NIR bands in the 2000–2500 nm region.…”
Section: Resultsmentioning
confidence: 99%
“…As most of the NIR bonds are overtone and combination bands of normal modes involving CH, OH, and NH bonds, there is the potential of NIR to monitor the structure of a protein. In fact, NIR has been extensively applied to the characterization of protein‐containing materials, including clinical, agricultural, and food applications 13–17. Recently, some studies have suggested that secondary structure information about proteins in the dried state could be obtained with NIR,18 but these reports did not compare native and denatured forms of a protein, so the utility of NIR for formulation development was not demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, moderate utility of predicting the NFC (R 2 = 0.83, SEP = 1.55% of DM) and fat content (R 2 = 0.81, SEP = 0.40% of DM) of TMR was observed using NIRS. Utility of NIRS to predict fat content of homogenized human diets (Almendingen et al, 2000) has been demonstrated; however, no literature references were found on the utility of NIRS to predict the NFC content of mixed human or animal diets.…”
Section: Methodsmentioning
confidence: 99%
“…Aufrere and Michalet-Doreau (1988) observed that NIRS could be used to predict in vitro DM digestibility (IVDMD) of forages, which is an indirect measure of animal performance. In mixed diets, Almendingen et al (2000) demonstrated that CP and fat content of homogenized human diets could be accurately predicted by NIRS. Likewise, White and Rouvinen-Watt (2004) developed robust NIRS equations to predict the DM, CP and fat content of mixed diets for mink.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral range considered in this work was relatively narrower than the 400-2500 nm or 1100-2500 nm ranges used in most of the past studies, and the nutrients considered in this study had broader range of values compared to those used by Togerson et al (2003), Almendingen et al (2000), Schwarze (1997), and Clark and Short (1994). In spite of the low RPD for cholesterol, the PLSR models developed in this study resulted in low standard errors, and high R 2 values, comparable to other reported studies.…”
Section: Refined Plsr Modelmentioning
confidence: 96%